Mixed connective tissue disease presenting as quadriparesis in a female (Indian Journal of Case Reports, 2018)
Mixed connective tissue disease (MCTD), or overlap syndrome, is a multisystem autoimmune disease characterized by a combination of clinical features similar to those of polymyositis, systemic sclerosis, and rheumatoid arthritis. MCTD patients present with a distinct rise (high titers) of anti-U1 ribonucleoprotein antibody in serum. Here, we present the case of a 45-year-old female who presented with subacute onset weakness on all four limbs and later on diagnosed as overlap syndrome with severe myositis.